Freshwater mollusk species of Itupararanga Reservoir, São Paulo, Brazil - Bianca Medeiros Vendramini; Eliane Pintor de Arruda (Check List, 2022)
The Itupararanga Reservoir, located within an environmental protection area, is an important water source that supplies four cities in the state of São Paulo. Samples of mollusks were collected in the reservoir to create an inventory of species and identify possible bioindicators. Thirteen species were identified: Diplodon caipira (Ihering, 1893), Anodontites trapesialis (Lamarck, 1819), Pisidium globulus Clessin, 1888, Pomacea figulina (Spix in Wagner, 1827), Omalonyx convexus (Heynemann, 1868), Drepanotrema cimex (Moricand, 1839), Biomphalaria tenagophila (d’Orbigny, 1835), Uncancylus concentricus (d’Orbigny, 1835), Stenophysa marmorata (Guilding, 1828), and Pseudosuccinea columella (Say, 1817), which are native to Brazil, and Corbicula fluminea (O.F. Müller, 1774), Melanoides tuberculata (O.F. Müller, 1774), and Physa acuta Draparnaud, 1805, which are invasive species. This is the first inventory of mollusks in this area, and this initial study will allow complementary research into populational ecology. Additionally, this inventory contributes records that clarify the areas of occurrence of the reported species.